NKX2-1 New Mutation Associated With Myoclonus, Dystonia, and Pituitary Involvement - Balicza, Péter; Grosz, Zoltán; Molnár, Viktor; Illés, Anett; Csabán, Dora; Gézsi, Andras; Dézsi, Lívia; Zádori, Dénes; Vécsei, László; Molnár, Mária Judit (Frontiers in Genetics, 2018)
Background: NKX2-1 related disorders (also known as brain-lung-thyroid syndrome or benign hereditary chorea 1) are associated with a wide spectrum of symptoms. The core features are various movement disorders, characteristically chorea, less frequently myoclonus, dystonia, ataxia; thyroid disease; and lung involvement. The full triad is present in 50% of affected individuals. Numerous additional symptoms may be associated, although many of these were reported only in single cases. Pituitary dysfunction was ambiguously linked to NKX2-1 haploinsufficiency previously. Case presentation: We examined two members of a family with motor developmental delay, mixed movement disorder (myoclonus, dystonia, and chorea) and endocrinological abnormalities (peripheric thyroid disease, and pituitary hormone deficiencies). Dystonia predominated at the father, and myoclonus at the daughter. The father had hypogonadotropic hypogonadism, while the daughter was treated with growth hormone deficiency. Both patients had empty sella on MRI. Candidate gene analyses were negative. Exome sequencing detected a pathogenic stop variation (NM_003317:c.338G>A, p.Trp113*) in the NKX2-1 gene. Conclusions: This case study has two highlights. 1) It draws attention to possible pituitary dysfunction in brain-lung-thyroid syndrome, and provide further evidence that this might be linked to loss of function of the NKX2-1 gene. 2) It underscores the importance of considering NKX2-1 related disorders in the differential diagnosis of myoclonus dystonia.